Reverse Logistics Systems: Persepsi dan Harapan Konsumen - Farida Pulansari; Dwi Sukma Donoriyanto; Nisa Masruroh (Institute of Research and Community Outreach - Petra Christian University, 2016)
Complaint is a signal that indicates important information directly by customers. Complaint will give valuable information to company to plan recovery strategies to maintain customer satisfaction and loyalty. Hence, electronic waste (E-waste) becomes a hot issue internationally, domestically and locally. There are many kind of regulations, strategy, methods or approach to minimize of E-waste. The goal of this research is design of house of reverse logistics (HRL) to understanding the customer needs and wants for reverse logistics (RL) implementation. This research adopted quality function deployment (QFD) method to construct the HRL. Differences among them are determination of the customer needs and wants. HRL insert five perspectives i.e. input, structure, process, output, and social and organization. In other hand, QFD only inserts consumer perspectives. The results showed the important factors of consumer dissatisfaction comes from: third-party services mechanism (20%), collaboration RL system (collection centers, recycling centers, disposal center; 10%), the standardization of servicing system (10%).